Advances in Genomics and Epigenomics of Social Insects - Greg J. Hunt (Frontiers Research Topics, 2017)
Social insects are among the most successful and ecologically important animals on earth. The lifestyle of these insects has fascinated humans since prehistoric times. These species evolved a caste of workers that in most cases have no progeny. Some social insects have worker sub-castes that are morphologically specialized for discrete tasks. The organization of the social insect colony has been compared to the metazoan body. Males in the order Hymenoptera (bees, ants and wasps) are haploid, a situation which results in higher relatedness between female siblings. Sociality evolved many times within the Hymenoptera, perhaps spurred in part by increased relatedness that increases inclusive fitness benefits to workers cooperating to raise their sisters and brothers rather than reproducing themselves. But epigenetic processes may also have contributed to the evolution of sociality. The Hymenoptera provide opportunities for comparative study of species ranging from solitary to highly social. A more ancient clade of social insects, the termites (infraorder Isoptera) provide an opportunity to study alternative mechanisms of caste determination and lifestyles that are aided by an array of endosymbionts. This research topic explores the use of genome sequence data and genomic techniques to help us explore how sociality evolved in insects, how epigenetic processes enable phenotypic plasticity, and the mechanisms behind whether a female will become a queen or a worker.